Arabic Language Document Steganography Based On Huffman Code Using DRLR As (RNG) (Al-Mansour Journal, 2022)
In this research the problem of ownership of text is processed in several methods. The secret message can be used for verification (ID). All other methods can hide a secret message or (ID) inside text. It can be found all these methods can change secret message when personal ownership is embedded in the text, this research offers problem solution by hiding in protocol in Arabic scripts. The new method depends on subtraction of cover text from original secret message different from original message to obtain the new secret message, to embedded into other texts. And this method uses two levels method to hide a new secret message. LinguisticSteganography covers all the techniques that deal with using written natural language to hide secret message. This research, presents a linguistic steganography for Arabic language documents, using Kashida and Fast Fourier Transform on the basis of using new technique which is Secret Message Compression (SMC) to obtain a new a secret message using dynamic random linear regression (DRLR) as location to hide a secret message. The proposed approach is an attempt to present a transform linguistic steganography using levels for hiding to improve implementation of kashida, and to improve the security of the secret message by using dynamic random linear regression (DRLR). The proposed algorithm has achieved typical steganography properties such as capacity, security, transparency, and robustness.
Keywords: Arabic Documents; Linguistic Steganography; Secret Message Compression; Huffman code; Dynamic Random Linear Regression; Kashida; Transform Basis